An examination of objectively-measured sedentary behavior and mental well-being in adults across week days and weekends - Gibson, Ann-Marie (PLoS One, 2017)
BACKGROUND: Limited research has explored the links between sedentary behaviour, mental health and quality of life. This study examines objectively measured sedentary behaviour and perceived mental health and quality of life across week days and weekends. METHODS: 42 adults (19M, 23F; mean age 38yrs (range 18–67) & BMI 24.8kg/m(2) (range 18.7–33.8) wore an activPAL monitor 24h/day for one week and completed the Hospital Anxiety and Depression Scale (HADS) and SF12 Health Survey. Average weekday and weekend day sitting time was computed. Differences between sitting (Group 1 = <8hrs/day, Group 2 = 8–10 hrs/day, Group 3 = >10hrs/day) and components of the HADS and SF12 health survey were examined using an ANCOVA with a measure of physical activity (step count) included as a covariate. RESULTS: Average sitting time on a weekday was 9hrs 29mins (range 5hrs 52mins to 12hrs 55mins) and 8hrs 59mins (range 4hrs, 07mins to 14hrs, 40mins) on a weekend day. There was a main effect (p<0.05) for weekday sitting time on total anxiety and depression (HADS) and mental health and vitality (SF12). Planned contrasts identified individuals in group 1 had lower anxiety and depression and higher mental health and vitality scores than individuals in groups 2 or 3 (p<0.05). No difference was found between individuals in group 2 and group 3 (p>0.05). No main effects were found for weekend sitting (p>0.05). CONCLUSIONS: Weekday sitting time below 8 hours/day is associated with better perceived mental health and quality of life.